ANALISIS KINERJA KENDALI OTOMATIS GREENHOUSE PIGGYBACK BERBASIS PLC DENGAN METODE IRIGASI SUMBU (WICK SYSTEM) - Gustiar Martua Siregar; Hamdani; Beni Satria (CV. Hawari, 2025)
This study aims to analyze the performance of an automated control system in a piggyback greenhouse that implements a Programmable Logic Controller (PLC) as the control center, using a wick irrigation system for the plants. A piggyback greenhouse is a multi-story greenhouse concept designed for space efficiency in urban agriculture. This system utilizes soil moisture, temperature, and light sensors to monitor environmental conditions, along with actuators such as water pumps and ventilation systems controlled by a PLC. The wick irrigation method was chosen for its efficiency and energy savings, as water is absorbed by the plants through capillary action. Tests were conducted in several environmental scenarios to assess the response and stability of the automated control system. The test results showed that the system was able to consistently maintain soil moisture within the optimal range of 60–80%, with an average response time of 3 seconds for pump activation. Furthermore, the use of a PLC allows for flexibility in control logic settings and operational efficiency. Overall, the PLC-based piggyback greenhouse system with wick irrigation has proven effective in improving agricultural environmental control and supporting small-scale precision agriculture concepts. This research can serve as a basis for further development in the application of automation technology in the modern urban agricultural sector.